PTEN Is Required for The Anti-Epileptic Effects of AMPA Receptor Antagonists in Chronic Epileptic Rats - Ji-Eun Kim (International Journal of Molecular Sciences, 2020)
α-Amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR) is one of the ligand-gated ion channels for glutamate, which is an important player in the generation and spread of seizures. The efficacy of AMPAR functionality is regulated by the trafficking, synaptic targeting, and phosphorylation. Paradoxically, AMPAR expression and its phosphorylation level are decreased in the epileptic hippocampus. Therefore, the roles of AMPAR in seizure onset and neuronal hyperexcitability in ictogenesis remain to be elucidated. In the present study, we found that AMPAR antagonists (perampanel and GYKI 52466) decreased glutamate ionotropic receptor AMPA type subunit 1 (GRIA1) surface expression in the epileptic rat hippocampus. They also upregulated phosphatase and tensin homolog deleted on chromosome 10 (PTEN) expression and restored to basal levels the upregulated phosphoinositide 3-kinase (PI3K)/AKT1 phosphorylations. Dipotassium bisperoxovanadium(pic) dihydrate (BpV(pic), a PTEN inhibitor) co-treatment abolished the anti-epileptic effects of perampanel and GYKI 52466. Therefore, our findings suggest that PTEN may be required for the anti-epileptic effects of AMPAR antagonists.